Efektivitas Priming pada Benih Jagung dalam Memperbaiki Perkecambahan pada Media Masam - Agustin, Noly; Agustiansyah, Agustiansyah; Timotiwu, Paul Benyamin; Kamal, Muhammad (Universitas Lampung, 2023)
The high Aluminum content in Ultisol soil is one of the main problems in maize cultivation starting from the germination phase to plant growth. Priming treatment on seeds is believed to be able to improve germination in a less favorable environment. The study was conducted to determine the effect of priming on the germination of corn seeds germinated in acid media containing aluminum. The study was arranged in a Completely Randomized Design (CRD) which was repeated four times. There were 8 treatments in this study, namely control/without priming, water priming, KNO3 0.1%, and 0.5, PEG-6000 5% and 10%, GA3 50 ppm and 100 ppm. The data were analyzed for variance and continued with a 5% LSD test using the R Studio statistic program. The results showed that 50 ppm GA3 priming was the best treatment for increasing corn seed vigor based on the variables of time of radicle emergence, time of emergence of plumules, growth speed, growth synchronously, vigor index, root length, coleoptile length, wet weight of normal sprouts, and dry weight of normal sprouts. Keywords:priming, corn, germination